Humanizing the Academic Advising Experience with Technology : An Integrative Review (Comparative & International Education Series, 2021)
The use of information and communication technologies, such as Zoom, Canvas, Blackboard, and Microsoft Teams, have dramatically revolutionized student learning and academic advising at the time of the COVID-19 global pandemic. This chapter builds on previous research to explore how humanizing academic advising with technology impacts student interaction, technological engagement, and the online community in a higher education context. We examine how current and future technological advancement can be leveraged to reach and support students and argue that the academic advising process needs to put human beings at the center of the student experience. This integrative review provides a snapshot into the higher education landscape that may garner future conceptualization of advising practices, implementations, and policies.How to cite this chapter:Liu, C., & Ammigan, R.  (2022). Humanizing the academic advising experience with technology: An integrative review. In  R. Ammigan, R. Y. Chan, & K. Bista, (eds), COVID-19 and higher education in the global context: Exploring contemporary issues and challenges (pp. 185-202). STAR Scholars. https://starscholars.org/product/covid-19-and-higed/